A CROSS-SECTIONAL CASE STUDY ON THE RELATIONSHIP BETWEEN REGULAR FEEDBACK AND EMPLOYEE PERFORMANCE AT EXCEL TRAINING INSTITUTE, NIMULE, SOUTH SUDAN. - Zaituni Namusisi; Edmand Bakashaba; Biho Leonard (Student's Journal of Health Research, 2023)
Background. The study aimed to determine the relationship between regular feedback and employee performance at Excel Training Institute Nimule South Sudan. Methodology. A cross-sectional case study research design was employed among the staff of Excel Training Institute. The study was conducted in Excel Training Institute Limited located in Nimule, Magwi sub-county at the border of Uganda and South Sudan. Simple random to give every employee an opportunity and a purposive sampling technique for respondents with in-depth information regarding the study variables were used to obtain 81 participants in the study. The researcher administered questionnaires and interview guides to get the information.  Results. Out of the 81 participants, findings showed there was a fair positive significant correlation (r=0.569, sig=0.000) between feedback and employee performance at Excel Training Institute- South Sudan. Conclusion. The organization schedules regular one-on-one meetings with employees to discuss their performance, provide constructive feedback, and offer guidance on improving and implementing a system where employees receive feedback from their managers, peers, and subordinates. Recommendation. The organization should embrace regular constructive feedback, criticism, regular performance evaluations, and one-on-one meetings between management and staff.